Potensi Ampas Kopi Dan Kulit Kopi Sebagai Bahan Baku Alternatif Pada Pakan Ikan: Potential Use Of Coffee Ground And Coffee Silver Skin As Alternative Ingredients In Fish Feed - Wastu Ayu Diamahesa; Nuri Muahiddah (LPPM Universitas Mataram, 2022)
The ever-increasing demand for and consumption of coffee from year-to-year results in a rise in waste, particularly coffee grounds and coffee skins. Multiple attempts have been made to utilize this waste in the cosmetics, pharmaceuticals, and industrial sectors. As a result of the waste's nutritious content, there is a significant potential for its usage as fish feed's ingredients. However, only a small number of researchers have examined the use of coffee grinds and coffee skins in aquaculture, particularly for tilapia (Oreochromis niloticus) and Olive flounder (Paralichthys olivaceaus). This article aims to provide an overview of the potential use of coffee grounds and coffee skin in the world of aquaculture, particularly fish feed, in terms of nutrients and their application in enhancing the quality of these raw materials utilizing a fermentation process aided by probiotic microorganisms.